GENDER INJUSTICE IN NAWAL AS-SA’DAWI'S SUQUUTH AL-IMAAM: AN IDEOLOGICAL FEMINISM ANALYSIS - Akmal Hibatullah Ramadhan; Yayan Rahtikawati; Rohanda Rohanda (Arabic Literature Department, 2024)
Gender injustice is a universal issue reflected in the novel Suquuth Al-Imaam by Nawal As-Sa’dawi. This study aims to identify the forms of gender injustice depicted in the novel and analyze them using the ideological feminist approach. The research employed a descriptive-analytical method with a literature study technique, focusing on text analysis of the novel based on various forms of gender injustice. The findings reveal that gender injustice in the novel is represented through marginalization, subordination, stereotyping, double burden, and violence. These injustices are not merely individual manifestations but are part of the patriarchal ideological structure legitimizing gender inequality both socially and institutionally. The ideological feminist approach exposes patriarchal control over women's bodies, roles, and statuses as a means to maintain male dominance. The novel serves as a critique of the patriarchal system and as a medium to promote gender awareness. This research contributes to feminist and literary studies by demonstrating that literature can be utilized to challenge unjust ideological structures.